Analisis Manajemen Risiko dengan Pelaku yang Tidak Menilai Berbahaya: Studi Kasus Hotel Atria Serpong - Taufiq Niko Purbayu; Nusa Setiani Triastuti (Jurnal Syntax Admiration, 2023)
Hotel Atria Serpong has been inaugurated since 2010, in terms of fulfilling a stylish concept so that in 2021 the facade of Hotel Atria Serpong will start to be renovated. This facade project with a height of 48.25 meters is a very risky job. Therefore researchers are interested in conducting research. The purpose of this research is analysis based on risk management based on real implementation data and secondary data on the documentation of each job.In determining the level of risk, researchers used a data processing tool based on matriculation from Permen PUPR No.10 yr.2021, with mean and validity using Spss v.12 software. Questionnaire data taken from 30 respondents were 4 contractor employees with a bachelor's degree background, 23 contractor workers with an educational background < high school, 1 foreman with a high school background and 2 hotel engineers with a bachelor's and vocational background. With the existence of invalid data as much as 9%, one of the reasons is the education of the respondents. Respondents of construction actors stated that risky things were considered not to be worried about risks, therefore the researcher validates with engineering validity data in the form of documentation photos.In general, the type of risk that will occur is falling from a height and the result is injury to death. The risk level resulting from high to moderate levels is the work of dismantling steel structures, painting the outer walls, installing roof truss structures, dismantling signage and installing ACP fins. The risk response is to hold routine briefings, use APD, carry out project SOPs and carry out supervision at any time. In conclusion there are no work accidents and implementation failures